1997
DOI: 10.1159/000147975
|View full text |Cite
|
Sign up to set email alerts
|

Architecture and the Division of Labor in the Extensor carpi radialis Muscle of Horses

Abstract: The extensor carpi radialis muscle of the horse is deceptive at first appearance. It has a fusiform shape similar to other forearm extensor muscles. The fiber arrangement also appears long and relatively parallel. However, it may contain two or more compartments that correlate with differing functional roles. Histochemical and immunocytochemical analysis of proximal and distal regions of the muscle (n = 9) demonstrate that the proximal portion of the muscle is composed of a mean of 13% type I, presumed slow tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
20
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 2 publications
4
20
0
Order By: Relevance
“…This group also exhibited reduced vertical displacement while trotting compared with walking (Table 2). Such 'spring dampening' while loading the Achilles tendon at speed reduces damaging vibrations and enhances forward propulsion with subsequent energy savings (Alexander, 2001;Hermanson, 1997;Reilly et al, 2007;Wilson et al, 2000Wilson et al, , 2001, which is consistent with our metabolic measurements (Fig. 3).…”
Section: Discussionsupporting
confidence: 89%
“…This group also exhibited reduced vertical displacement while trotting compared with walking (Table 2). Such 'spring dampening' while loading the Achilles tendon at speed reduces damaging vibrations and enhances forward propulsion with subsequent energy savings (Alexander, 2001;Hermanson, 1997;Reilly et al, 2007;Wilson et al, 2000Wilson et al, , 2001, which is consistent with our metabolic measurements (Fig. 3).…”
Section: Discussionsupporting
confidence: 89%
“…Pennation angle in equine muscle has received less attention in the literature (Hermanson and Cobb, 1992;Hermanson, 1997). Pennation angle is important because highly pennated muscles typically have more short muscle fibers arranged in parallel.…”
Section: Discussionmentioning
confidence: 99%
“…The flexor carpi mm) and short (7-14 mm) fibers. Hermanson (1997) c noted 92 mm long fiber bundles in the proximal region of extensor carpi radialis, but did not quantify muscle fiber length within these bundles.…”
Section: Physiological Cross-section Area (Pcsa)mentioning
confidence: 97%
“…Many locomotor muscles in mammals are composed by "neuromuscular compartments," defined as nonoverlapping sections within the muscle, each innervated by an individual muscle nerve branch (English and Letbetter, 1982) and each containing motor unit territories with a unique array of physiological attributes (English et al, 1993). Many studies have reported a clear correspondence between neuromuscular partitions, muscle architectural designs, and muscle fiber type distribution (Burkholder et al, 1994;Hermanson, 1997;Gellman et al, 2002), suggesting an independence of motor control and division of labor between compartments. The term "muscle fiber type regionalization" is a newly developed concept that signifies the presence of regional intramuscular differences in fiber type composition (Kernell, 1998).…”
mentioning
confidence: 99%